The influence of duration and control of diabetes mellitus with the results of phacoemulsification surgery on senile cataract sufferers with diabetes mellitus in Yogyakarta - Setyandriana, Yunani; Putri, Dananvia Servanda Kamilia (Institute of Computer Science (IOCS), 2024)
Diabetes Mellitus (DM) is a metabolic disorder that can be established if the GDP level is ≥ 126 mg/dl or the GDS or TTGO level is ≥ 200 mg/dl. Currently phacoemulsification technique has been widely used to treat cataracts because of its faster increase of visual acuity, lower changes in astigmatism, and low complication rates during surgery and post-operatively. The study aimed to determine the influence of duration and control of DM with the results of phacoemulsification surgery on senile cataract sufferers with DM in Yogyakarta. The study, which used an analytical observational method with a cross-sectional design, was conducted at the Eye Polyclinic of a Private Hospital in Yogyakarta by taking a sample of 77 patients. Consecutive sampling was carried out to collect the sample. Logistic regression method was applied for the study test. We used a logistic regression test and obtained significance values of 0.643 and 0.432 (P>0.05) which suggested no influence of duration and control of DM and the results of phacoemulsification surgery. It was stated that there was no influence between the duration and control of DM on the results of phacoemulsification surgery.